A 3-year-old child presenting with a cervical mass: diagnostic dilemma - Buthukuri, Sunayana; Marda, Sachin; Gowda, Sreehari; Sethi, Shweta; Aregala, Praneeth (International Surgery Journal, 2025)
Ganglioneuromas are benign tumors that originate from the sympathetic chain and are composed of ganglion cells and nerve fibres. These are most often located in the mediastinum (20%), retroperitoneum (10%), and adrenal gland (30%). We report a case of a 3-year-old female child presenting with a neck mass and ptosis for 4 months. A computed tomography (CT) scan of the neck was done, which showed well defined ovoid lesion in the neck suggestive of a neurogenic tumor. Image-guided fine-needle aspiration cytology (FNAC) was done, which was given as a ganglioneuroma. With imaging and histopathological guidance, we have done meticulous excision under general anaesthesia (GA). Although ganglioneuromas are common neurogenic tumors, their occurrence in the cervical region is very rare. Ganglioneuromas should be considered as part of the differential diagnosis for pediatric soft tissue tumors of the head and neck. The diagnosis for ganglioneuromas in the cervical region can only be ascertained with postoperative pathologic examination, and excision is considered the only effective treatment modality known so far, which may cause Horner’s syndrome at times. However, patients have a favorable prognosis without recurrence overall.